Plasmonic enhancing nanoantennas for photodetection - Hewageegana, P.; Stockman, M.I. (Infrared Physics & Technology, 2007)
This paper discusses the use of plasmonic nanostructured systems as nanoantennas for photodetection. Even though semiconductors and their heterostructures have many useful properties and widely used in photodetection, their electron density is very small compared to that of metals and, therefore, they have low absorption cross sections. The idea of using metal nanostructured antennas is to combine the high optical responses of metals with the functional electric properties of semiconductors.
Keywords: Nanooptics; Nanosystems; Local fields